Solecisms of Sight: Specular Speculations. - Morris, Robert (October)
Presents the text of a speech given by Robert Morris at the Whitney Museum of American Art on November 29, 2001, which deals with the Finch College Project, a film installation made in 1969 that was represented at the Whitney Museum exhibition 'Into the Light: The Project Image in American Art 1964-1977' from 2001 to 2002.